Integrative Omics Analysis Reveals a Limited Transcriptional Shock After Yeast Interspecies Hybridization - Hovhannisyan, Hrant; Saus, Ester; Ksiezopolska, Ewa; Hinks Roberts, Alex J.; Louis, Edward J.; Gabaldón, Toni (Frontiers in Genetics, 2020)
The formation of inter-specific hybrids results in the coexistence of two diverged genomes within the same nucleus. It has been hypothesized that negative epistatic interactions and regulatory interferences between the two sub-genomes may elicit a so-called “genomic shock” involving, among other alterations, broad transcriptional changes. To assess the magnitude of this shock in hybrid yeasts, we investigated transcriptomic differences between a newly formed Saccharomyces cerevisiae x Saccharomyces uvarum diploid hybrid and its diploid parentals, which diverged ~20 million years ago. RNA-Seq based allele-specific expression analysis indicated that gene expression changes in the hybrid genome are limited, with only ~1-2% of genes significantly altering their expression with respect to a non-hybrid context. In comparison, a thermal shock altered six times more genes. Furthermore, differences in expression between orthologous genes in the two parental species tended to be diminished for the corresponding homeologous genes in the hybrid. Finally, and consistent with RNA-Seq results, we show a limited impact of hybridization on chromatin accessibility patterns, as assessed with ATAC-Seq. Overall, our results suggest a limited genomic shock in newly formed yeast hybrid, which may explain the high frequency of successful hybridization in these organisms.